The case of the case of mistaken identity - Barnett, Mac.; Rex, Adam (New York : Simon & Schuster Books for Young Readers, 2010)
Twelve-year-old Steve Brixton, a fan of Bailey Brothers detective novels, is mistaken for a real detective and must elude librarians, police, and the mysterious Mr. E as he seeks a missing quilt containing coded information.
Booklist
Bulletin (Center for Children's books)
School Library Journal
Booklist, October 2009
Bulletin (Center for Children's books), January 2010
Library Media Connection, November 2009
Keywords: Books and reading -- Juvenile fiction; Librarians -- Juvenile fiction; Mistaken identity -- Juvenile fiction; Police -- Juvenile fiction; Quilts -- Juvenile fiction; Books and reading -- Fiction; Humorous stories; Librarians -- Fiction; Mistaken identity -- Fiction; Mystery and detective stories; Police -- Fiction; Quilts -- Fiction; Books and reading -- Fiction; Humorous fiction; Librarians -- Fiction; Mistaken identity -- Fiction; Mystery fiction; Police -- Fiction; Quilts -- Fiction; Humorous fiction; Mystery fiction